2015
DOI: 10.1210/en.2014-1584
|View full text |Cite|
|
Sign up to set email alerts
|

Two Zebrafish hsd3b Genes Are Distinct in Function, Expression, and Evolution

Abstract: HSD3B catalyzes the synthesis of δ4 steroids such as progesterone in the adrenals and gonads. Individuals lacking HSD3B2 activity experience congenital adrenal hyperplasia with imbalanced steroid synthesis. To develop a zebrafish model of HSD3B deficiency, we characterized 2 zebrafish hsd3b genes. Our phylogenetic and conserved synteny analyses showed that the tandemly duplicated human HSD3B1 and HSD3B2 genes are coorthologs of zebrafish hsd3b1 on chromosome 9 (Dre9), whereas the gene called hsd3b2 resides on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…hsd3b2 transcript levels decrease at the 4 somites stage and remain very low (Figure J). The hsd3b2 transcript patterns are consistent with the described role of hsd3b2 in early embryogenesis . cyp21a2 transcript is almost undetectable until primordium‐5 (24 hpf) (Figure K).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…hsd3b2 transcript levels decrease at the 4 somites stage and remain very low (Figure J). The hsd3b2 transcript patterns are consistent with the described role of hsd3b2 in early embryogenesis . cyp21a2 transcript is almost undetectable until primordium‐5 (24 hpf) (Figure K).…”
Section: Resultssupporting
confidence: 86%
“…Thus, it is tempting to speculate that only the later highly expressed genes, which are also expressed in the larval interrenal gland, have functions similar to those in mammals with respect to glucocorticoid biosynthesis during larval stages. Indeed, recent studies have demonstrated that cyp11a2 , fdx1b and hsd3b1 , but not their corresponding paralogues, are involved in cortisol synthesis in zebrafish . In addition, we have recently shown a key role for cyp21a2 in glucocorticoid biosynthesis in zebrafish …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations